Etherification studies on chalcone derivatives with series of bromoalkane 1 - Boireh, Gunsiong (Universiti Malaysia Sarawak, UNIMAS, 2008)
This research is focusing on the etherification studies of chalcone derivatives with series of bromoalkanes which are bromohexane ( C6H13Br), bromoheptane (C7H15Br), bromooctane(C8H17Br), and bromononane (C9H19Br). There are two different strategy used in this research. The first strategy involved the etherification of 4-hydroxybenzaldehyde followed by synthesis to chalcone derivatives.The second strategy was the synthesis of chalcone using 4- hydroxybenzaldeyde as a starting material followed by etherification to chalcone derivatives. From this research the first strategy give the highest yield.